Métodos tradicionales de caza y Directiva de aves silvestres. Comentario al asunto C-900/19, One Voice, STJUE de 17-03-2021 - Agustín García Ureta (Revista Vasca de Administración Pública, 2021)
This comment examines a judgment of the Court of Justice of the European Union (CJEU) concerning prohibited hunting methods, in particular, adhesive-covered twigs and the exception set out in Directive 20097147, on the conservation of wild birds. This directive allows, under strictly supervised conditions and on a selective basis, the capture, keeping or other judicious use of certain birds in small numbers. The judgment examines the notion of «selective basis» and draws a distinction between lethal and non-lethal hunting methods. Nevertheless, it questions the use of adhesive-covered twigs, demanding that any national decision be based on the best available scientific knowledge. The conditions imposed by the CJEU severely restrict the use of this method.